Midwifery Care for Postpartum Mothers with Discomfort Pain of Episiotomy Stitches at PMB Ernyadi Sidoarjo: Asuhan Kebidanan Pada Ibu Nifas dengan Ketidaknyamanan Nyeri Luka Jahitan Episiotomi di PMB Ernyadi Sidoarjo - Bella Milenia; Hanik Machfudloh (Academia Open, 2021)
The pain due to the episiotomy is not the same, the intensity of the pain is different. This pain is due to the active peripheral nociceptors, which are receptors in particular, which are responsible for delivering to noxious stimuli. This midwifery care is aimed at dealing with complints to Mrs.P history of episiotomy at BPM Ernyadi Sidoarjo with the method of collecting initial data to evaluation the results obtained by Mrs.P a history of episiotomy. Did not find any difficulties at the time the care was given this study was carried out at 2 hours of the puerperium the mother gave birth on January 12, 2020 at 19.15 spontaneously an episiotomy was carried out on the indication of a stiff perineum according to the theory the conclusion from the case study with the initial data collection method to the eva;uation of the problem Mrs.P all the findings and all the actions that have been implemented, Mrs there was no difference between the theory and no signs of infection in the episiotomy suture scars.